PENGUATAN KINERJA BUDIDAYA TAMBAK DALAM RANGKA PENCAPAIAN KETAHANAN PANGAN - Lelono, Eko Joko; Susilowati, Indah (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2010)
This research on production efficiency and availability of brackishwater pond pro- duction in Parigi Moutong whether in a state of food insecurity or not. This study used a stochastic frontier production function analysis and cost benefit ratio. As a result, production of aquaculture ponds in the study sites were technically not effective, but feasible to proceed. Cultivation was not efficient because of the positive and significant influence of production inputs of land, seed, and labor. Production inputs such as fertilizer, feed, experience, lime, technology, fisheries counsellor were not significant The availability of pond products produced by processes that have not been efficient and food insecurity due to consumption of fish per capita per year is greater than the amount of production. Strengthening the performance of the pond to achieve food security needs to intensification and diversification. Intensification of land from two crops to be harvested three times a year.